THE EFFECT OF PROFITABILITY AND LEVERAGE ON TAX AVOIDANCE IN MANUFACTURING COMPANIES IN THE CONSUMER GOODS INDUSTRY SECTOR LISTED ON THE INDONESIAN STOCK EXCHANGE IN 2019-2021 - Nanditha Myesa Haidar; Citra Mariana (Jurnal Ekonomi, 2023)
Because its contribution to the state revenue and expenditure budget (APBN) is greater than other sources of revenue (other than taxes). This study has a goal, namely to obtain results regarding whether there is an effect of profitability and leverage on tax avoidance. This research was conducted on industrial goods industry sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period with a total population of 129 company financial reports. By using purposive sampling and outlier analysis techniques, a sample of 75 company financial reports was produced. data analysis in this study used panel data regression analysis using a significance level of 5%. the results of testing the T test with Eviews 12 software show that profitability is 0.021 and leverage is 0.000, it can be shown that these results are smaller than the specified significance level. then, it can be concluded that profitability and leverage have a significant effect on tax avoidance.